2010
DOI: 10.1097/cej.0b013e328333d0b3
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trend of tumor size and downstaging in breast cancer in Iran: results of a 15-year study

Abstract: The aim of this cross-sectional study was to show the characteristics of breast cancer across a period of 15 years according to pathological records in Tehran, Iran. In the year 1985, a 20-year study was designed and developed in five major hospitals in Tehran to study the burden and characteristics of breast cancer in Iran. This study is based on the data collected from 1986 through 2000. SPSS version 13 was used for statistical analysis. In this study, 1612 female breast cancer records were reviewed. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Nevertheless, the rate of lymphatic invasion (63.15%) in our cases shows a similar propensity for lymphatic metastases in VY women and other patients [45.5% (Mousavi et al, 2008) and 70% (Harirchi et al, 2010) in two different studies in all ages]. Our study shows a high level of hormone receptor negative tumors as expected, and a 20% (3 out of 15) for triple negative cancers.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the rate of lymphatic invasion (63.15%) in our cases shows a similar propensity for lymphatic metastases in VY women and other patients [45.5% (Mousavi et al, 2008) and 70% (Harirchi et al, 2010) in two different studies in all ages]. Our study shows a high level of hormone receptor negative tumors as expected, and a 20% (3 out of 15) for triple negative cancers.…”
Section: Discussionsupporting
confidence: 61%
“…It has been shown that breast cancer affects Iranian women at least one decade younger than the female population in developed countries (Harirchi et al, 2004;Bidgoli et al, 2010;Kolahdoozan et al, 2010), with an incidence of 20-25% for cases under 40 and about 5% for age under 30 (Mousavi et al, 2008;Harirchi et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…They also found high rate of LNI at the time of presentation. Indeed, the frequency of advanced BC in Iran is high and despite all considerable improvements in the diagnostic tools during past decades (Harirchi et al, 2010), the frequency of advanced BC rose in the last phases of study. Even, if we had the metastatic status of the study population, patients might be placed in higher stages, as well.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BC among young Asian women is moderate but is increasing and may be more than two fold higher than western countries (Agarwal et al, 2007;Karihtala et al, 2010). Previous studies showed that BC has become the most 6906 on the recent changes in age distribution for primary and secondary prevention of BC (Mousavi et al, 2008;Harirchi et al, 2010). Aging is considered as one of the main risk factors for developing new BC events (Gennari et al, 2004;Molino et al, 2006;Benz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although the amount of stage shift cannot be straightforwardly linked to breast cancer mortality, it can be regarded as an important proxy for the performance of early detection programmes. 8,[10][11][12][13][14][15][16] Particularly in LMICs where the stage distribution of newly diagnosed breast cancer cases is often poor, the amount of stage shift is an essential performance indicator that could help LIMCs to decide on which breast cancer control programmes to implement.…”
Section: Introductionmentioning
confidence: 99%